JAMMU & KASHMIR & THE POLITICS OF ARTICLE 370: SEEKING LEGALITY FOR THE ILLEGITIMATE - Hoskote, Amitabh; Hoskote, Vishakha A (PEOPLE: International Journal of Social Sciences, 2017)
Article 370 of the Indian Constitution stipulates autonomy for the state of Jammu and Kashmir (J&K). Terms of the Article have remained mired in controversy owing its unequal dispensation within the framework of free India. This paper examines Article 370 and the validity of politics attached to it, based on four specific arguments. First, the Genesis of Article 370 spawns inequality in India. Second, its Retention implies festering of contentious issues. Third, its Ramifications forge inequality within J&K. Fourth, how Politics over Article 370 only seek limited leverage from it. These arguments have been examined through an engagement with primary and secondary sources and views analyzed in different traditions. The case universe comprises views across a spectrum of opinion. An interpretivist approach classifies this debate in the larger context of Continuation or Revocation of Article 370, based on the research question whether Article 370 has worked in the manner envisaged, or has aggravated inequality and fuelled growth of conflict in J&K.